(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2022)
In the context of the Covid-19 pandemic in Brazil, the clash and resistance of the press in the face of attacks and aggressions carried out by denialists was evident. The documentary Cercados, produced by Globoplay, object of analysis of this work, portrays the behind-the-scenes challenges of journalistic coverage in the first year of Covid-19 in Brazil. Supported by concepts of enunciation theory and television studies, the objective is to reflect on the effects of meaning produced by the audiovisual text and its contribution to critical reflection on the scenario of disinformation, as well as the relevance of journalism as an institution of the democratic system. The results indicate that the organization of discourse, marked by the aesthetics of self-referentiality, allows the enunciatee to enter the universe of journalistic production and identify with the thematic roles played by journalists.